Achieving Edge Consensus in Hybrid Multi-AgentSystems: Scaled Dynamics and Protocol Design (European Journal of Pure and Applied Mathematics, 2025)
In contrast to existing research on consensus problems that primarily addresses the node dynamics of multi-agent systems, this study focuses on achieving consensus among the states of edges within a network. Initially, the scaled consensus of edge dynamics in hybrid multi-agent systems is investigated for both undirected and directed topologies. Subsequently, necessary and sufficient conditions are derived for both directed and undirected topologies to facilitate the design of consensus protocols aimed at resolving edge consensus challenges. Finally, numerical examples are provided to substantiate the effectiveness of the theoretical results.
Keywords: Hybrid multi-agent systems, scaled consensus, edge consensus problem, spanning tree, directed and undirected topology